(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The traumatic factor head injury due to road traffic accident (RTA) is a very common feature in the cases of fatal injuries, which is a permanent damage to lifetime just like a disease. In our study, the total autopsy conducted is 3730, in which males (58.32%) are out in number than females (41.68%). Total number of fatal head injury due to RTA is 1281 (34.34%). Most vulnerable age is 21–30 years comprising of 365 (28.49%) cases. On sex-wise comparison, 1013 (79.08%) males were injured than females (268 (20.92%)). Most of the incidents occurred between the time 1200 and 1800 hours comprising of 429 (33.49%) cases. Married victims are out in number comprising of 809 (63.15%) cases; 633 (49.42%) of victims died on the way to hospital, which is the highest, followed by 339 (26.46%) victims died in hospital, least number of deaths occur on the spot comprising of 309 (24.12%) cases. Two-wheeler occupants were the commonest group of victims comprising of 830 (64.79%) cases, pedestrian comprising 115 (8.98%) of total cases. Most common offending vehicle is heavy motor vehicle comprising 783 (61.12%) of all types of vehicle cases.